Design of devops solution for managing multi cloud distributed environment - Jambunathan, Baskaran; Y. Kalpana, Dr (International Journal of Engineering and Technology, 2018)
DevOps is the emerging field in the area of IT infrastructure management and cloud automation. Organization are spending time and money in terms of continuous improvement and optimization in their infrastructure management and finding to avenues for efficiency and produc-tivity improvement, reduce redundancy and optimise cost in the area of development and deployment of their enterprise application. More importantly, organisation have multiple environment to manage and hence need to have a mechanism to continuously monitor and optimize operational task and improve collaboration with various teams across organization. In addition, many companies are migrating or migrated on to cloud, some are having multiple cloud environments across regions, and hence managing it is even more difficult and need to have a mechanism to address the key challenges and risk in managing devOps in multicloud. . In this article, we would like to discuss the key challenges and how it can be addressed in a multi cloud environment and proposing an integrated solution addressing all challenges with right set of tools and framework design which enables devops in multi cloud efficiently.
Keywords: Cluster Management; Docker; Flocker; Fabric8; Jenkins; Kubernetes; Rancher; Micro Services; Wrecker